Videoclip “Quiero” - Cruzcaiman: experiencia de realización audiovisual - Pacora Sánchez, Gabriela Sofía (2023)
In the report presented below, the creative process of the conceptual video clip of the song “quiero” by the band cruzcaiman is detailed. The different stages of preproduction, realization and postproduction will be addressed from a directive, photographic and artistic perspective. It was elaborated with the goal of establishing a visual style for the group and as a broadcast medium for the band’s first single. In regards to the client’s requirements, they solicited that a conceptual and artistic vision prevails throughout the project instead of a merely narrative one.